PENGGUNAAN KARTU ANGKA DALAM PENGENALAN KONSEP BILANGAN PADA ANAK KELOMPOK B DI TA AL-IKHLAS (UNISMA, 2022)
The background of this research is the phenomenon of success in preschools to understanding the concept of numbers to their students in class.The name of the school is TA Al-Ikhlas. TA Al-Ikhlas used number card media to introduce the concept of numbers to his students, until make his students in class happy and enthusiastic to learning the concept of numbers, and can make them fast to understanding the concept of numbers. This research is a qualitative research. The subjects of research is the principal and teacher of group B in TA Al-Ikhlas. And the object of research is the use of number card media to introducing the concept of numbers in group B. Data collection techniques is observation, interviews, and documentation. The data analysis technique is data reduction, data presentation and conclusions. The results of this research are TA Al-Ikhlas in introducing the concept of numbers by providing material about time, date, month, and year. In using number cards to introduce the concept of numbers to group B children, the teacher does this by introducing the concept of numbers and number cards and give assignments to each student to answer and connecting number cards with the appropriate number concept.